Above 100 nJ solitons from a passively mode-locked thulium-doped fiber oscillator. (26th June 2015) - Zhou, Wei; Shen, Deyuan
Asbtract: We report on stable nanosecond pulses with a non-symmetrical shape and high energy from a passively mode-locked thulium (Tm) fiber oscillator in the purely anomalous dispersion regime. The laser generated wave-breaking-free solitons with pulse widths increased from 460 ps to 3.15 ns by boosting the pump strength. The solitons yielded an output average power of 1.1 W, a repetition rate of 10.63 MHz, and a pulse energy up to 103 nJ at the maximum available pump power. By removing the free-space components, the pulse energy was further scaled to 268 nJ at a 11.2 MHz repetition rate. The corresponding polarization-locked vector solitons (PLVS) were also observed.